Incidentally Diagnosed Osteopoikilosis: A Case Report - Mustafa Reşorlu; Ozan Karatağ; Canan Akgün Toprak; Davut Döner (Galenos Yayinevi, 2017)
Osteopoikilosis is a rare bone dysplasia. Patients are generally asymptomatic and are frequently identified during radiological imaging by coincidence. The epiphysis and metaphysis of the long bones, the phalanges and pelvic bones are the localizations which frequently involved. It appears as oval or round, homogeneous, symmetrical, uniform, radio-opacities. Osteoblastic metastases, mastocytosis, tuberous sclerosis and Paget's disease should be considered in differential diagnosis.